Antibacterial Peptide Protocols - Shafer, William; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1997)
In Antibacterial Peptide Protocols, leading authorities review for the first time in one volume all the major biochemical, molecular, bacteriological, and physical techniques available to assess antimicrobial peptides. These state-of-the-art methods ensure easily reproducible results in such important procedures as the isolation and characterization of antimicrobial peptides, the molecular characterization of genes encoding antimicrobial peptides, and the use of expression systems to isolate peptides. Bioassays and microbial genetic techniques are also included, as are antibacterial assays as the final readout system. These methods detailed in Antibacterial Peptide Protocols will play an important role in the treatment of infectious diseases, particularly with the increasing problem of multidrug-resistant microbes and the relative dearth of new antibiotics being provided by pharmaceutical companies.
Origins and Development of Peptide Antibiotic Research -- Origins and Development of Peptide Antibiotic Research -- Isolation and Characterization of Antibacterial Peptides -- HPLC Methods for Purification of Antimicrobial Peptides -- Strategies for the Isolation and Characterization of Antimicrobial Peptides of Invertebrates -- Big Defensin and Tachylectins-1 and -2 -- Tachyplesin and Anti-Lipopolysaccharide Factor -- Circular Dichroism Studies of Secondary Structure of Peptides -- Analytical Ultracentrifugation Studies of Association of Peptides -- NMR Characterization of Amphipathic Helical Peptides -- Molecular Biology of Antibacterial Peptides -- Laboratory Production of Antimicrobial Peptides in Native Conformation -- An Approach Combining Rapid cDNA Amplification and Chemical Synthesis for the Identification of Novel, Cathelicidin-Derived, Antimicrobial Peptides -- Molecular Biological Strategies in the Analysis of Antibiotic Peptide Gene Families -- Assay Systems for Studying Antibacterial Peptides -- Designer Assays for Antimicrobial Peptides -- Interaction of Cationic Peptides with Bacterial Membranes -- The Genetic Basis of Microbial Resistance to Antimicrobial Peptides -- Assay of Antibacterial Activities of the Bactericidal/Permeability-Increasing Protein in Natural Biological Fluids -- Assay Systems for Measurement of Chemotactic Activity -- Neutralization of the In Vivo Activity of E. Coli-Derived Lipopolysaccharide by Cationic Peptides.
Keywords: Bacteriology; Biochemistry; Bacteriology; Biochemistry, general